The Impact of Timing of Dialysis Initiation on Mortality in Patients with Peritoneal Dialysis. Issue 7 (December 2015) - Kim, Hyung Wook; Kim, Su-Hyun; Kim, Young Ok; Jin, Dong Chan; Song, Ho Chul; Choi, Euy Jin; Kim, Yong-Lim; Kim, Yon-Su; Kang, Shin-Wook; Kim, Nam-Ho; Yang, Chul Woo; Kim, Yong Kyun
Background: The impact of timing of dialysis initiation on mortality is controversial in patients with peritoneal dialysis (PD). In this study, we analyzed the impact of timing of dialysis initiation on mortality in the incident PD population. Methods: Incident patients with PD were selected from the Clinical Research Center (CRC) registry for end-stage renal disease (ESRD), a prospective cohort study on dialysis in Korea. Patients were categorized into 3 groups according to the estimated glomerular filtration rate (eGFR) at the initiation of PD using the Modification of Diet in Renal Disease (MDRD) equation. Group A was defined as eGFR < 5 mL/min/1.73m 2, group B as eGFR 5 – 10 mL/min/1.73m 2, and group C as eGFR > 10 mL/min/1.73m 2 . Cox regression analysis was used to calculate the adjusted hazard ratio (HR) of mortality with group B as the reference. The primary outcome was all-cause mortality. Results: A total of 495 incident PD patients were included. The number of patients in group A was 109, group B was 279, and group C was 107. The median follow-up period was 23 months. Multivariate Cox regression analysis showed that group A had a significantly higher risk of all-cause mortality compared with group B (HR 4.13, 95% confidence interval [CI], 1.55 – 11.03, p = 0.005) after adjustment for age, gender, cause of ESRD, serum albumin level, diabetes mellitus, and cardiovascular disease. There was no significant difference in mortality between group C and group B (HR 1.50, 95% CI, 0.59 – 3.80, p = 0.398) after adjustment for clinical variables. Conclusion: An eGFR < 5 mL/min/1.73m 2 at the initiation of PD was a significant risk factor for death, while an eGFR >10 mL/min/1.73m 2 at the initiation of PD was not associated with improved survival compared with an eGFR of 5 – 10 mL/min/1.73m 2 at the initiation of PD.